Association of Attention Deficit/Hyperactivity Disorder With Events Occurring During Pregnancy and Perinatal Period - Liu, Jianbo; He, Yuqiong; Shen, Yanmei; Zhou, Yuanyue; Meng, Tiantian; Xiao, Bo; Cui, Xilong; Fang, Yumin; Lu, Jianping; Xiang, Yu-Tao; Luo, Xuerong (Frontiers in Psychology, 2021)
Background: The relationship of events occurring during pregnancy and perinatal period with attention deficit/hyperactivity disorder (ADHD) is not clear. Thus, the focus of the current study was to examine the effects of events occurring during pregnancy and perinatal period on ADHD. Methods: A two-phase cross-sectional study was performed across 13 schools in Changsha and Yiyang cities from March to December, 2014. We preliminarily screened all students using CBCL and established the diagnosis using Mini International Neuropsychiatric Interview for Children and Adolescents (MINI-KID) and the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV). A total of 3,418 questionnaires were effectively completed in this study. Results: History of threatened abortion (TA) [odds ratio (OR): 1.707 (1.201–2.426)] and neonatal asphyxia (NA) [OR: 2.497(1.225–5.09)] showed a positive association with ADHD. On subgroup analysis, TA [OR: 2.216 (1.458–3.369)] (vs. No-TA) was a risk factor for ADHD without comorbidity; instrumental delivery [OR: 2.748 (1.057–7.142)] (vs. natural birth) and NA [OR: 2.789 (1.222–6.361)] (vs. healthy) were risk factors for ADHD in the subgroup of ADHD with comorbidity; TA (vs. no-TA) and NA (vs. healthy) were risk factors for ADHD among male students [ORs: 2.232 (1.439–3.462) and 2.808 (1.115–7.068), respectively], while low birth weight (LBW) (vs. normal birth weight) was a risk factor [OR: 2.054 (1.063–3.967)] for ADHD among female students. Conclusion: TA was a risk factor for ADHD in the absence of comorbid conditions; instrumental delivery and NA were risk factors for ADHD in the subgroup of ADHD with comorbidity; TA and NA were risk factors for ADHD among male students. LBW was a risk factor for ADHD among female students.